Early childhood curriculum policies and practices in Singapore: The case of glocalisation. Issue 2 (February 2021) - Yang, Weipeng; Li, Hui; Ang, Lynn
Globalisation has been transforming early childhood care and education worldwide since the turn of this millennium. The early childhood sector in Singapore is no exception. Its early childhood curriculum has inevitably been influenced by Eastern and Western cultures and has developed into a unique hybrid over the years. This special issue collects six articles covering topics on inclusive education, curriculum frameworks, infant–toddler care, curriculum-based teacher research, social-emotional learning, and bilingual language and literacy. A book review about early childhood curriculum in Chinese societies is also included. All these articles have jointly presented a snapshot of the 'glocal' situation of early childhood curriculum in Singapore, with a focus on the challenges and suggestions for policy and practical improvements.